MULTIMODAL ANALYSIS OF VISUAL DESIGN IN LECTURER POWERPOINT (PPT) DURING THE TEACHING PROCESS - Yohana Gracela Br Sitompul; Harpen H.P Silitonga; Sahat Taruli Siahaan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language as a social semiotic system is not only manifested through verbal forms, but also through visual, gestural, audio, and spatial modes that work simultaneously in multimodal communication. This study analyzes the application of multimodality—particularly visual design in lecturers' PowerPoint presentations—and its contribution to learning effectiveness in higher education. Using a descriptive qualitative approach, data were collected through slide documentation, classroom observation, interviews, and student perception questionnaires, then analyzed based on representational, interactive, and compositional meanings. The results show that the consistent use of color, typography, layout, images, and diagrams helps structure information, emphasize important concepts, and reinforce lecturers' verbal explanations. Visual functions vary according to context: clarifying abstract concepts in Pragmatics courses and supporting idea development in Cultural Text Writing. Students reported increased understanding, attention, and reduced cognitive load, although text density and visual balance remained challenges. Overall, PowerPoint is effective when visual design is aligned with pedagogical goals and student academic levels.